X-Men. Apocalypse [videorecording (DVD)] - Singer, Bryan, 1965-; McAvoy, James, 1979-; Fassbender, Michael, 1977-; Lawrence, Jennifer, 1990- (20th Century Fox Home Entertainment, 2016)
After the re-emergence of the world's first mutant, world-destroyer Apocalypse, the X-Men must unite to defeat his extinction level plan.